Avaliação da força de atrito estático em braquetes autoligados e convencionais estudo in vitro - Oliveira, Luiz Felipe Durand de (2011)
The aim of this study was to evaluate, by means the axial pull-out strength, the influence of using conventional metal brackets and metal and ceramic self-ligating, in the intensity of the frictional force generated when associated with orthodontic wires of circular and rectangular sections of different diameters. Three types of brackets were used in this work: metallic conventional (G1); metallic self-ligating (G2) and ceramic self-ligating (G3). Bars were made of polyethylene (10 cm long x 3.5 cm thick x 3.5 cm wide) where three brackets were bonded (canine, first and second premolars rights) previously aligned and leveled. The groups of brackets were associated with orthodontic wires, stainless steel (Cr-Ni) of circular and rectangular sections in three dimensions, F1: 0.020" circular, F2: 0.017 x 0.025 , F3: 0.019" x 0.025" rectangular, resulting Groups: G1F1, G1F2, G1F3, G2F1, G2F2, G2F3, G3F1, G3F2 and G3F3. For each type of bracket were prepared 10 specimens. All groups were tested in a universal testing machine (EMIC DL 2000). easurements of friction were obtained every 0.5 mm distance to travel a total of 5 mm. The values found were submitted to the analysis of Kruskal-Wallis and Tukey. The results showed that self-ligating brackets showed lower friction resistance when compared to conventional brackets used with circular and rectangular wire sections. The differences in the values of the friction encountered between conventional and selfligating brackets have a direct influence of association with the section of wire used.